MASTer cell: chief immune modulator and inductor of antimicrobial immune response - Suárez Vázquez, Tomás Alejandro; López López, Nallely; Salinas Carmona, Mario César (Frontiers in Immunology, 2024)
Mast cells have long been recognized for their involvement in allergic pathology through the IgE-mediated degranulation mechanism. However, there is growing evidence of other 'non-canonical' degranulation mechanisms activated by certain pathogen recognition receptors. Mast cells release several mediators, including histamine, cytokines, chemokines, prostaglandins, and leukotrienes, to initiate and enhance inflammation. The chemical nature of activating stimuli influences receptors, triggering mechanisms for the secretion of formed and new synthesized mediators. Mast cells have more than 30 known surface receptors that activate different pathways for direct and indirect activation by microbes. Different bacterial strains stimulate mast cells through various ligands, initiating the innate immune response, which aids in clearing the bacterial burden. Mast cell interactions with adaptative immune cells also play a crucial role in infections. Recent publications revealed another 'non-canonical' degranulation mechanism present in tryptase and chymase mast cells (MCTC) in humans and connective tissue mast cells (CTMC) in mice, occurring through the activation of the Mas-related G protein-coupled receptor (MRGPRX2/b2). This receptor represents a new therapeutic target alongside antibiotic therapy. There is an urgent need to reconsider and redefine the biological role of these MASTer cells of innate immunity, extending beyond their involvement in allergic pathology.